Cadre posyandu empowerment and apparatus village in monitoring status nutrition, food provision of additional pregnant women and children to prevent stunting - Lubis, Halinda Sari; Santi, Devi Nuraini (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The low nutritional status of pregnant women during pregnancy can result in various adverse effects for both mother and baby. Poor nutritional status in infants allows problems / developmental delays. In Langkat District the number of toddlers weighed in 2017 was 98,822 people and there were 189 (0.2%) who were below the Red Line (BGM). Malnutrition sufferers found in 2017 were 110 people. Another nutritional status indicator is Iron Nutrition Anemia (AGB) which is an effort to reduce it by giving iron tablets (Fe) as many as 90 tablets during pregnancy in Langkat Regency which is still below the national percentage of 78.69%. The prevalence of stunting toddlers in Langkat Regency in 2018 is 23.3%. For this reason, empowerment of cadres and village officials to monitor the nutritional status of pregnant women and toddlers to prevent stunting. Through increased knowledge and skills of cadres and village officials to achieve a reduction in the incidence of stunting in improving the nutritional status of pregnant women and toddlers can be done with nutritional surveillance by monitoring activities: PMT recovery, provision of vitamin A, TTD, Taburia, Zinc, Stimulation. The socialization was carried out on 26 June 2019 in the Hall of Karang Rejo Health Center, Langkat Regency. Training was held on June 26, 2019 in the Hall of Karang Rejo Health Center in Langkat Regency to improve the knowledge and skills of cadres and village officials to achieve a reduction in the incidence of stunting in improving the nutritional status of pregnant women and toddlers.